Análisis filogenético del murciélago hematófago Desmodus rotundus en el Valle del Cauca Colombia - Castro, Fernando Favian Castro; Flores, Jaime Eduardo Muñoz; Uieda, Wilson [UNESP] (Universidad Nacional de Colombia, 2016)
Phylogenetic analyses of the hematophagous bat Desmodus rotundus were performed in villages belonging to Valle del Cauca, Cauca and Amazonas regions. Samples were mainly collected at hematophagous bat shelters located in Victoria, Águila, Obando, Cartago, Zarzal, San Pedro, Cerrito and Palmira villages belonging to Valle del Cauca region, two samples at Mercaredes which belong to Cauca, two samples at Puerto Nariño which is part of Amazonas region. Epithelial tissue samples were collected from bat's patagium, and submitted to PCR using primers 16 SL and 16SH amplifying mitochondrial DNA of 50 vampires, these products were sequencing resulting in eight haplotypes being the most common presented in 43 individuals. Two methods to reach maximum likelihood and parsimony were used. GENBANK sequences of mitochondrial markers s16 rRNA from Brazil, Venezuela and Costa Rica were used for comparison. Higher similarity between vampire bats from Valle del Cauca and Cauca region, located in the southwest Colombia and vampire bats from Costa Rica and Venezuela was found. In the present study the genetic profiles correlated with the phylogeographic aspects of different populations was performed and a connection between different haplotypes of existing clades was found according to the phylogenetic tree and haplotype net, possible being generated during hematophagous bats migration over the mountain-chain and rivers crossing Colombia.
Phylogenetic analyses of the hematophagous bat Desmodus rotundus in Valle del Cauca, Colombia
Keywords: 16SH; 16SL; Clades; DNA; GENBANK; Haplotypes; Patagium; PCR